COMBINE MIDAZOLAM-FENTANYL-KETAMIN FOR EVISERATION SURGERY IN PATIENT WITH MULTIDRUG ALERGY IN ACUTE ON CHRONIC EXCACERBATION OF HIPERSENSITIVITY REACTION - Panji, Putu Agus Surya; Sudjana, Ida Bagus Gde; Suranadi, I Wayan; Tanggono, Aninda (Bali Journal of Anesthesiology, 2018)
ABSTRACTMultidrug Alergy is a relatively rare imunology abnormality. Generally, it caused by congenital genotype and influence with environment. After treated the acute on chronic exacerbation of hypersensivity tipe 1, and the inflamation can alleviate, the patient schedule of eviseration oculi dextra with general anesthesia. And the opthamologist curious about the proceddure because eviseration need antibiotic to wash the oculi, but there are no antibiotic saved for the patient. For general anesthesia, the patient has no history so we canât predicted about the anesthetic drugâs allergy. We choose combine ketamine-midazolamadn fentanyl to facilitate the anesthesia. Ketamine significantly reduces the production of inflammatory cytokines without affecting the production of anti-inflammatory cytokines. Fentanyl is the opioid which is the most rarely caused allergy and have strong potential. Midazolam can help the sedation